(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Mild to severe pain or discomfort on injection of propofol used for the induction of anaesthesia is often observed in pediatric population. Objectives: This study was designed to compare the efficacy of methylprednisolone and lignocaine in reducing the pain of propofol injection in patients scheduled for pediatric surgery. Methods: Total 135 children scheduled for elective surgery were divided into three groups: saline (group S, n=45), lignocaine 20 mg (Group L, n=45) and methylprednisolone 125 mg diluted into 2 ml of distilled water (Group MP, n=45). Drugs were administered after tourniquet application and occlusion was released after 1 min and 25% of the total dose of propofol (2 mg/kg) was administered at the rate of 0.5 ml/s. Pain on propofol injection was evaluated by four-point verbal rating scale. Data were analyzed by using SPSS version 21. Results: The overall incidence of pain was 65.9% in the saline group, 23.8% in the lignocaine group and 30.5% in the methylprednisolone group. Intensity of pain was significantly less in patients receiving methylprednisolone and lignocaine than those receiving saline (p< 0.05). Conclusion: Pre-treatment with intravenous methylprednisolone was found to be as effective as lignocaine in reducing propofol injection-induced pain. DS (Child) H J 2019; 35(1) : 59-62